Analysis of The Use of ITIL Methodology for Service Management: A Review of The Scientific Literature of The 2015 - 2020 - Estefanny L. CONDORI CUCCHI; Liset S. RODRIGUEZ BACA (Communications of International Proceedings, 2021)
Companies have deficiencies in the management of services provided to users, the advancement of technology has improved the efficiency of this management, implementing the Information Technology Infrastructure Library (ITIL) not only improves efficiency, but also reduces costs, improves performance, effectiveness and increases productivity in the service by providing timely responses to the attention of users. ITIL is the standardization of the definition of processes oriented to the quality of service, adapting to the needs of the areas that use Information Technology (IT). The reasons for conducting this study indicate that ITIL has benefits in the management of services that companies provide to their respective users. This research is a systematic review, which aimed to answer the following questions: what are the benefits of using ITIL methodology in service management in companies and what are the most common inefficiencies in Service Management, for which 50 scientific articles related to the topic were taken and are published between 2015 to 2020, which were extracted from different academic sources such as: IEEE Xplore, Scopus, ScienceDirect, Scielo, Springer Link and Redalyc. The result of this research shows the benefits of using the ITIL methodology and the most common inefficiencies in companies. In conclusion, the most important benefit is to improve the integration of IT with the business giving 50.70% of the collected items and the most common inefficiencies in Service Management in companies are user dissatisfaction and skills gap obtaining an equal percentage.
Keywords: ITIL methodology; ITIL Methodik; IT Service Management; “ITIL METHODOLOGY” AND “SERVICE MANAGEMENT”